A multi-period mathematical model for simultaneous optimization of materials and energy on the refining site scale. (1st April 2015) - Zhang, B.J.; Liu, K.; Luo, X.L.; Chen, Q.L.; Li, W.K.
Graphical abstract: Integration between process units and utility systems. Highlights: Process units and utility systems are integrated for total refining site optimization. An MINLP model is presented to optimize materials and energy simultaneously. Energy requirements of process units are formulated based on transshipment model. The method does a good tradeoff between the material profit and energy cost. Abstract: A process system is designed for material transformations that produce certain functional chemicals while usually consuming large amounts of energy. Materials in process systems have long been the major focus of investigation to achieve better economic performance. Rising energy prices and stricter limitations on greenhouse gas emissions have also led to greater attention on energy savings. The configuration of process units in a total refining site has a great impact on both material and energy requirements. The simultaneous optimization of materials and energy is highly important for an enterprise. Hence, material and energy integration is proposed in this study for a total refining site to minimize costs. A mixed integer nonlinear programming model is developed that includes four parts: production planning for materials, energy requirements of process units on the basis of pinch analysis, operational planning for utility systems, and balance of utility streams in total sites. An industrial example is studied to demonstrate the performance of the proposed model and the advantages of simultaneous optimization of materials and energy. Significant economic benefits are demonstrated by the simultaneous optimization in this study.